NFLUENCE OF USE DIRECT OBJECT OF TECHNICAL ABILITY TO WRITE POETRY CLASS VII SMP NEGERI 2 SUTERA - Facita, Yulia; Yasnur, Asri; Marni, Silvia (Pendidikan Bahasa Indonesia, 2014)
This study aimed to describe and analyze the influence of the direct object of the technique s ability to write poetry class VII SMP Negeri 2 Sutera review of the ability of students to use diction (choice of words) , style and imaging in writing poetry . This type of research is quantitative research with experimental methods . Population in this research is a class VII SMP Negeri 2 Sutera subjects enrolled in 2013/2014 a total of 180 students. Sample size was 28 respondents, taken with purposive sampling technique . The data of this study is the ability to write poetry scores grade students of VII SMP Negeri 2 Sutera before and after using the technique of direct objects . Data is analyzed and then performed a t- test to determine the effect of the use of the direct object of the technique s ability to write poetry VII SMP Negeri 2 Sutera . The results of this study are : First , the average skills of students at pretest (early test) is 59.15 . Second , the average student skills at posttest (final test) is 75.03 . Third , there is a significant influence of the direct object of the techniques of poetry writing skill VII SMP Negeri 2 Sutera , because â¥ . Thus, the direct object is very accurate technique used in learning to write short stories.